Dynamics of Water Diffusion Changes in Different Tissue Compartments From Acute to Chronic Stroke—A Serial Diffusion Tensor Imaging Study - Alegiani, Anna Christina; MacLean, Simon; Braass, Hanna; Gellißen, Susanne; Cho, Tae-Hee; Derex, Laurent; Hermier, Marc; Berthezene, Yves; Nighoghossian, Norbert; Gerloff, Christian; Fiehler, Jens; Thomalla, Götz (Frontiers in Neurology, 2019)
Background and Purpose The immediate decrease of the apparent diffusion coefficient (ADC) is the main characteristic change of water diffusion in acute ischemic stroke. There is only limited information on the time course of diffusion parameters in different tissue compartments of cerebral ischemia. Materials and Methods In a longitudinal study, we examined 21 patients with acute ischemic stroke by diffusion tensor imaging within 5 hours after symptom onset, three hours later, two days, and one month after symptom onset. Acute diffusion lesion and the fluid-attenuated inversion recovery (FLAIR) after two days were used as volumes of interest to define infarct core, lesion growth, and reversible acute diffusion lesion. For all diffusion parameters ratios between the stroke lesion VOIs and the mirror VOIs were calculated for each time point. ADC ratio, fractional anisotropy ratios, and eigenvalues ratios were measured in these volumes of interest and in contralateral mirror regions at each time points. Results In the infarct core, ADC ratio (0.772) and all eigenvalues ratios were reduced on admission up to one day after stroke and increased after one month (ADC ratio 1.067). Within the region of infarct growth time course of diffusion parameter changes was similar, but delayed. In the brain area with reversible diffusion lesion, a partial normalization of diffusion parameters over the time was observed, while after one month diffusion parameters did not show the signature of healthy brain tissue. There were significantly different trends for all parameters over time between the three tissue compartments. Conclusion Diffusion tensor imaging displays characteristic changes of water diffusion in different tissue compartments over time in acute ischemic stroke. Even regions with reversible diffusion lesion show diffusion signatures of persisting tissue alterations.